2001
DOI: 10.1164/ajrccm.163.6.2004175
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pathophysiologic Phenomenon in Cachexic Patients with Chronic Obstructive Pulmonary Disease

Abstract: Cachexic patients with chronic obstructive pulmonary disease (COPD) show abnormalities of the autonomic nervous system (ANS), neuroendocrine function, and energy expenditure. Leptin has been implicated in the regulation of ANS, neuroendocine function, and thermogenesis in humans. We assessed the physiologic significance of the circadian rhythm of circulating leptin using power spectrum analysis of heart rate variability (HRV) in nine cachexic male patients with COPD, eight noncachexic patients with COPD, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(18 citation statements)
references
References 40 publications
1
14
0
3
Order By: Relevance
“…Likewise, in our meta-analysis, circulating leptin levels were correlated with nutritional parameters in COPD patients. Four articles [17,30,35,44] reported that circulating leptin levels decreased in COPD patients with lower BMI compared to healthy controls, which was not consistent with the small study of Takabatake et al [31], who reported that no difference was found between stable COPD patients and healthy controls. In addition, there was no difference in either circulating leptin levels or BMI between noncachexic COPD patients and healthy controls.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Likewise, in our meta-analysis, circulating leptin levels were correlated with nutritional parameters in COPD patients. Four articles [17,30,35,44] reported that circulating leptin levels decreased in COPD patients with lower BMI compared to healthy controls, which was not consistent with the small study of Takabatake et al [31], who reported that no difference was found between stable COPD patients and healthy controls. In addition, there was no difference in either circulating leptin levels or BMI between noncachexic COPD patients and healthy controls.…”
Section: Discussionmentioning
confidence: 88%
“…Eker et al [19] found that in stable COPD patients leptin levels were low and the frequency of insulin resistance was high compared with the controls, although no difference in body FM was determined between the study populations. In other studies where COPD patients and controls were well matched for age, gender and BMI, the circulating leptin levels were not significantly different between stable COPD patients and healthy controls [17,24,25,30,31,32]. However, Gaki et al [33] demonstrated that leptin levels were higher in COPD patients who used inhaled corticosteroids.…”
Section: Resultsmentioning
confidence: 95%
“…By contrast, we opted to study 3 clearly defined groups of COPD patients with a mixed male-female population. The latter point is particularly relevant when studying leptin, for instance, where normal females have been shown to have an approximately 3-fold higher leptin level than males [33], while investigation of leptin levels in COPD were principally determined in males [24, 32, 34]. Indeed, development of cachexia in COPD was previously suggested to be attributed to a cytokine-leptin link when the plasma levels of TNF-α and leptin were correlated [32].…”
Section: Discussionmentioning
confidence: 99%
“…The molecules receiving the greatest amount of attention are TNF-a, IL-1b, IL-6, C-reactive protein, and ROS and reactive nitrogen species (RNS). There may also be a link between inflammation and low leptin levels [34,35].…”
Section: Energy Imbalancementioning
confidence: 99%